Penentuan Alternatif Instalasi Pengolahan Air Limbah Di Desa Sayati, Kabupaten Bandung - Eka Wardhani; Adila Shalahuddin Anur; Salsabila Nurul Shofa Annisa; Zeihan Niswanurrahim; Yalka Sabila; Harashta Haifa Zahra (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The construction of a wastewater treatment plant (WWTP) in Sayati Village is still required in order to dispose of the village's wastewater in an appropriate manner. One potential location for wastewater disposal is the Cikahayangan River. However, the discharge of sewage into the Cikahayangan River results in water pollution, which in turn disrupts the river's natural functions. It is imperative that Sayati Village devise a WWTP that can effectively and efficiently treat wastewater, while also adapting to the existing conditions of the village over the next few years. This is crucial to prevent any adverse impacts from water pollution. The BOD/COD ratio for Sayati Village is 0.809, indicating that the wastewater is treated biologically. The unit selected from the scoring method is activated sludge. However, the land available in Sayati Village is limited, so the WWTP unit refers to the 2022 Sanimas Technical Instructions, which describe a compact WWTP for 100 families with a land availability of 3 meters in width. The domestic wastewater treatment plant (WWTP) processing unit planned for Sayati Village, Margahayu District, consists of primary, secondary, and tertiary domestic processing units. The secondary processing unit selected is an anaerobic filter, which is in accordance with the 2022 Sanimas Technical Guidelines. The units that will be planned in Sayati Village are a bar screen, a grease trap, a screw pump, a grit chamber, an equalization tank, an anaerobic filter, a disinfection unit, and a sludge processing unit.